A Case Study of Institutional Reform Based on Innovation Diffusion Theory Through Instructional Technology - Szabo, Michael; Sobon, Sonia A (Canadian Journal of Learning and Technology, 2003)
A theory-based system of educational reform through instructional technology, the Training, Infrastructure and Empowerment System (TIES), was developed and piloted in a research university during the late 1990s. In 2001, a research study was conducted on this implementation using qualitative methodology. Interviews were conducted with 12 participants who represented 4 different stakeholder groups. Some of the themes to emerge were: (a) Vision for instructional technology, (b) learning technologies and alternative delivery systems, (c) adoption of innovation, (d) general challenges and (e) lessons learned. Discussion includes implications of these themes for reform of education as they relate to a theoretical reform framework. Suggestions for further research are also identified.